A commentary on victimization and gender in white-collar crime - Dodge, Mary (Crime, law and social change, 2025)
The study of victimization and gender in white-collar crime presents numerous challenges. While many scholars argue that white-collar crime has no boundaries related to gender, race, ethnicity, socioeconomic status, or other defining human characteristics, sex and gender require further exploration. This commentary addresses women’s healthcare as a potential argument that a gender gap exists between the treatment of women and men in victimization. As consumers and reproducers, women face substantial and unique difficulties that increase the risk of pharmaceutical, medical, and consumer harm and crimes. Though men face many of the same unsafe working conditions, environmental dangers, and medical fraud, focusing on reproductive health and justice is essential to understanding widespread white-collar crime victimization. Women are more likely to be harmed by corporations and professionals because of birth control, medical devices, cosmetic products, and plastic surgeries. This essay acknowledges the importance of intersectionality but concentrates on how women are marketing targets of a patriarchal society that covets profit over safety. Reproductive injustice, stereotypical societal expectations of women, and capitalism in the United States often result in higher levels of harm against women. This commentary on corporate greed, regulatory failure, and unscrupulous medical behavior disguised as "cure-alls" demonstrates the need for establishing global databases, policies, and regulations that further our endeavors to recognize and reduce the continued use of women as guinea pigs based on greed and indifference by white-collar offenders.